Dampak Diskriminasi Ras Terhadap Tokoh Utama Dalam Cerpen Rihlah Ghurbah Karya ‘Awad Al-Nawasreh; Analisis Sosiologi Sastra - Syarifuddin Syarifuddin; Rahmah Zakiyah (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2022)
This study aims to describe the impact of racial discrimination on the main character in the short story "Rihlah Gharibah" by 'Awad Al-Nawasreh. Awad Al-Nawasreh managed to present an interesting and relevant story to the social conditions of the black community which has become a hot topic in recent times. This study uses a qualitative descriptive method with the main document object of the short story "Rihlah Gharibah". Important data and information collected and studied in this study are in the form of words, phrases and sentences that contain elements of the impact of racial discrimination contained in short stories. The data collection techniques are reading, recording, and analyzing documents with a sociology of literature approach as a framework of thinking. The results obtained from this study have been racial discrimination in this short story and have an impact on the main character in the short story. The impact on the main character is in the form of inferiority, social isolation and depression